Financial Stability In The Banks And Its Impact On Performance "A Study Of The Traditional Private Banks Listed On The Damascus Securities Exchange" - بعبع جمال; منذر مرهج (Latakia University Journal - Economic and Legal Sciences Series, 2023)
Banks are considered one of the main factors in supporting economic growth and financing businesses in Syria.With the passage of time and the escalation of economic and financial challenges in the country, the financial stability of banks has become vital to ensuring the sustainability of the banking sector and achieving the desired financial performance. Hence the importance of conducting an applied study to assess the relationship between financial stability in banks and their performance. The research community consisted of private banks in Syria after the exclusion of Islamic banks from 2007 to 2021, and their number reached /11/ The results of the research showed that there is a statistically significant relationship between the level of financial stability of private banks in Syria and the level of their performance. at a significant level of 5%. The results also showed the existence of a positive correlation between them, as the financial stability of private banks in Syria explains 18.86% of the change in their level of performance. The study showed that the arithmetic average of the level of financial stability of private banks in Syria indicates that the banks studied in the research sample are located in a low-risk area, also known as the safe area.